Research and analysis of fluorescent magnetic particle inspection of steam turbine rotor blade. Issue 2 (March 2021) - an, Jie
Abstract: The operating conditions of turbine rotor blades are complex and changeable, and the probability of defects is high, which puts forward higher requirements for the professionalism, safety, stability and convenience of magnetic particle inspection personnel. How to find the deficiencies in the magnetic particle inspection of blades and improve it to better adapt to the field inspection has become the focus of attention. This paper mainly describes the process of fluorescent magnetic particle inspection, compares the similarities and differences of magnetization specifications in three domestic standards, analyzes the problems found in the process of fluorescent magnetic particle inspection and makes corresponding improvement, and adopts reasonable optimization scheme to improve the reliability of fluorescent magnetic particle inspection. After demonstration test and field application, the improved fluorescent magnetic particle inspection can give full play to its advantages, achieve the purpose of rapid, accurate inspection and continuous improvement; on this basis, different inspection platforms can be established to inspect different parts, improve the universality and inspection efficiency of magnetic particle inspection, which is conducive to the promotion and application of magnetic particle inspection in the field of nuclear power.